Antennas for Emerging 5G Systems - Sayidmarie, Khalil H.; McEwan, Neil J.; Excell, Peter S.; Abd-Alhameed, Raed A.; See, Chan H. (International journal of antennas and propagation, 2019)
[...]they derive an exact closed-form expression for energy efficiency. [...]simulation results are given to validate the theoretical analysis and show that a substantial EE gain can be obtained over the proposed precoding scheme without large performance loss. [...]an intracluster power allocation algorithm is developed to maximize the power-difference in each cluster: this is beneficial to improve the successive interference cancellation (SIC) performance of the strong user. The results of numerical simulations are given to verify the effectiveness of the proposed method. [...]results indicate that the proposed method gives a more accurate DOA estimation of both the nonuniform noise and off-grid cases compared to a state-of-the-art DOA estimation algorithm.